Counseling and prenatal diagnosis in facioscapulohumeral muscular dystrophy: A retrospective study on a 13‐year multidisciplinary approach. Issue 3 (20th April 2022) - Di Feo, Maria Francesca; Bettio, Cinzia; Salsi, Valentina; Bertucci, Emma; Tupler, Rossella
Abstract: Background and Aims: This is the first national population‐based report about prenatal diagnosis for families with a history of facioscapulohumeral muscular dystrophy (FSHD), a complex hereditary disease. The incomplete disease penetrance and the phenotypic heterogeneity observed in carriers of D4Z4 alleles of reduced size, the FSHD molecular hallmark, make the estimate of genetic risk problematic. Methods: We considered all requests of preconception counseling and prenatal diagnosis received between January 2008 and December 2020 by the genetic counseling service associated with the Italian National Registry for FSHD (INRF). A multidisciplinary team managed the clinical and molecular data of each family. Results: Between 2008 and 2020, 60 couples required preconception counseling (PC) for FSHD. In 52 couples was observed at least one partner carried a D4Z4 reduced allele (DRA). Out of these 52 couples, 47 had a follow‐up visit routine yearly. Out of these 47, 26 (55.3%) couples had children: eight asked for prenatal diagnosis (PND), two had assisted reproduction by heterologous in vitro fertilization (IVF), and 16 did not require further assistance. Regarding PND, 50 prenatal analyses were performed for 36 couples. The test resulted positive in 27 pregnancies, 12 (44.4%) were terminated, and 15 (55.6%) were carried to term. Conclusion: The different choices made by the couples show the importance of an integrated approach to support genetic counseling for FSHD. These results remark the relevance of the clinical and molecular investigation of the extended family, preferably before conception.